Influence of Advertisement in social media Towards Purchasing Decision: A Study with Special Reference to Chennai City South Zone - Chandrasekaran, E.; Sudha, S. (International Journal of Membrane Science and Technology, 2023)
The usage of societal media for marketing objectives is a contemporary business trend that has been studied in recent literature. The aim of this study is to investigate the impact of social media advertising on customers’ purchase decisions. The research aims to investigate the importance given by consumers towards social media and investigate the association between societal media importance and Social media advertisements. At the same time to know the connotation of societal media importance including societal media usage, societal media trust, and purchasing decisions with the mediation effect of societal media advertisements. The sample was obtained through the use of convenience sampling. The sample size of this research is 200 the data were collected from users on societal media in Chennai’s south from a range of age groups. The study identifies a clear link between the significance of societal media and consumer purchasing behavior. Through societal media marketing, there is also a nexus between the importance of societal media and consumer purchase decisions.